Idiopathic Macular Telangiectasia Associated with Large Soft Drusen and Retinal Angiomatous Proliferation - Claudio Campa; Perri Paolo (Journal of Ophthalmic Science, 2016)
Idiopathic macular telangiectasia type 2 is a rare retinal condition usually characterized by parafoveal telangiectatic vessels, hyperplastic pigment plaques and seldom a full thickness macular hole or a retinal neovascularisation. Herein we describe an atypical presentation of this disease. Methods Review of the patient’s clinical and angiographic records. Results A 87-year-old white man was diagnosed with idiopathic macular telangectasia type 2. Ophthalmological and angiographic examination disclosed telangiectasia of the parafoveal capillaries together with extensive bilateral granular soft drusen and unilateral retinal angiomatous proliferation (RAP). Initially photodynamic therapy with verteporfin (PDT) and subsequently intravitreal injections of bevacizumab were used to treat RAP lesion. This approach provided visual acuity stabilization up to 24 months. Conclusion This case of ours shows that drusen may be a feature of macular teleangiectasia type 2. It also emphasizes that PDT and anti-VEGF therapy are both safe and effective for treating neovascular complications of this disease.
Keywords: drusen